1979
DOI: 10.7326/0003-4819-90-3-293
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcal Pharyngitis: Diagnosis by Gram Stain

Abstract: Group A beta-hemolytic streptococci were isolated from 49 (10.4%) of 472 patients with pharyngitis. Throat culture results, interpreted by five observers of varying experience, showed the mean sensitivity, specificity, and predictive value of a positive Gram-stained smear of pharyngeal secretions as 73%, 96%, and 71%. Assignment to a high-risk group by clinical algorithm gave sensitivity, specificity, and predictive value of only 45%, 83%, and 23%. The Gram-stained smear is the most accurate method of early di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1981
1981
2000
2000

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…These empiric therapy scales were corroborated by Komaroff and colleagues, who found that if 3 of 3 clinical markers, including fever, tender adenopathy, and exudate, were present, therapy was suggested, as subsequent cultures revealed a 30% to 45% incidence of GABHS (15). However, an analysis of physicians' clinical estimates of disease likelihood found that only 10% of patients treated empirically were subsequently diagnosed with culture-proven streptococcus (22). Thus, even if 100% of clinical markers associated with pharyngitis are present, streptococcal disease occurs in fewer than 50% of patients encountered (23).…”
Section: Diagnosismentioning
confidence: 90%
See 2 more Smart Citations
“…These empiric therapy scales were corroborated by Komaroff and colleagues, who found that if 3 of 3 clinical markers, including fever, tender adenopathy, and exudate, were present, therapy was suggested, as subsequent cultures revealed a 30% to 45% incidence of GABHS (15). However, an analysis of physicians' clinical estimates of disease likelihood found that only 10% of patients treated empirically were subsequently diagnosed with culture-proven streptococcus (22). Thus, even if 100% of clinical markers associated with pharyngitis are present, streptococcal disease occurs in fewer than 50% of patients encountered (23).…”
Section: Diagnosismentioning
confidence: 90%
“…Laboratory evaluation correlates leukocytosis or systemic white blood cell count greater than 8,500 with streptococcal infection (20). A Gram's stain analysis of pharyngeal exudate has demonstrated a 73% sensitivity and 96% specificity in the diagnosis of GABHS (22). A relatively new diagnostic modality is the rapid strep screen in which streptococcal antigen extracted from a throat swab is exposed to latex agglutination or an ELISA (enzyme-linked immunoassay analysis) reaction (21).…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…The score gives a predicted probability of group A streptococcal pharyngitis in relation to the prevalence of the disease in the population. Adjusted for a 5% prevalence of group A streptococcal pharyngitis (4.7% in our popula¬ tion), the corresponding probabilities of a positive culture for the symptom scores 0,1,2,3, and 4 are 0.6%, 1.7%, 4.5%, 11.4%, and 26%, respectively.2 The actual percentage of positive cultures in our patients with 0,1, 2, 3, and 4 pos¬ itive findings in any combination was compared with the predicted likelihood.…”
Section: Patients Materials and Methodsmentioning
confidence: 99%
“…Because diagnosis on clinical grounds alone is difficult, a reliable method for the early recognition of streptococcal pharyngitis would be helpful. Methods which have been proposed include the use of clinical syndromes' 1 and algorithms,2 Gram, 3,4 Wright,' and immunofluorescent staining',' of pharyngeal secretions, and the use of a scoring system. 8.9 This study was undertaken to evaluate the usefulness of a scoring system developed in an Eastern pediatric practice for the early diagnosis of streptococcal pharyngitis by house nffB~~rs.…”
mentioning
confidence: 99%